2016
DOI: 10.5812/ircmj.24319
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Complete Blood Count Parameters and Urinary Stone Disease

Abstract: BackgroundComplete blood count (CBC) parameters may associated with multiple diseases. Urinary stone disease is common public problem. Predictive value of CBC parameters may be associated with urinary stone diseaseObjectivesTo analyze the association between complete blood count (CBC) parameters and urinary stone disease.Patients and MethodsThis study was a retrospective observational study of 3,099 patients who were admitted to the urology outpatient clinic or diagnosed with urinary stone disease in the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
2
3
2
Order By: Relevance
“…A univariate and bivariate analysis showed that biochemical parameters such as NLR and RDW were statistically related to urinary stone disease. These results are in line with a previous investigational study which showed a positive association of RDW, mean platelet volume and WBC with urinary stone disease prediction [14]. Another noteworthy literature alluded that NLR appeared to be a potentially independent useful in ammatory biomarker in patients with kidney stones, and could be useful parameter as a new in ammatory marker for monitoring disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A univariate and bivariate analysis showed that biochemical parameters such as NLR and RDW were statistically related to urinary stone disease. These results are in line with a previous investigational study which showed a positive association of RDW, mean platelet volume and WBC with urinary stone disease prediction [14]. Another noteworthy literature alluded that NLR appeared to be a potentially independent useful in ammatory biomarker in patients with kidney stones, and could be useful parameter as a new in ammatory marker for monitoring disease.…”
Section: Discussionsupporting
confidence: 91%
“…Demiray et al reported the association of elevated RDW with several in ammatory diseases. Higher RDW levels resulted in an increased risk of urinary stone disease due to in ammation of the uroepithelium [14]. In accordance with this, present study revealed the association of higher RDW and lower lymphocyte with stone prognosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, MPV value was significantly high in hematuria patients than in the control group in our study. In some studies, it was reported that the MPV value was effective in evaluating the clinic of patients in some patients with GIS bleeding [39,46]. Unlike our study, in another study conducted on menstrual bleeding, which has a different bleeding focus, the MPV value was found to be lower than the controls [47].…”
Section: Discussioncontrasting
confidence: 87%
“…Studies have shown that inflammation and infection affect some blood indices [7,8,14] that could be used by physicians as diagnostic markers in diagnosing infectious diseases, including RDW, PDW, ESR (erythrocyte sedimentation rate), and CRP (C-reactive protein) [15,16] . To diagnose common infections, immune cells are counted, especially neutrophils [17,18] .…”
Section: Introductionmentioning
confidence: 99%